3(2t-3)=6(t+3)

Simple and best practice solution for 3(2t-3)=6(t+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2t-3)=6(t+3) equation:


Simplifying
3(2t + -3) = 6(t + 3)

Reorder the terms:
3(-3 + 2t) = 6(t + 3)
(-3 * 3 + 2t * 3) = 6(t + 3)
(-9 + 6t) = 6(t + 3)

Reorder the terms:
-9 + 6t = 6(3 + t)
-9 + 6t = (3 * 6 + t * 6)
-9 + 6t = (18 + 6t)

Add '-6t' to each side of the equation.
-9 + 6t + -6t = 18 + 6t + -6t

Combine like terms: 6t + -6t = 0
-9 + 0 = 18 + 6t + -6t
-9 = 18 + 6t + -6t

Combine like terms: 6t + -6t = 0
-9 = 18 + 0
-9 = 18

Solving
-9 = 18

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| y-55=146 | | 4.56-7.48= | | 0.14(y-1)+0.08=0.02y-1.8 | | 770/55*x=42 | | x/2=193 | | (4x/x^2-25)=(20/x^2-25)-(3/x-5) | | 282*3/x=47 | | 6x+3=5x+9-x | | 3x-64=-7 | | y=6/5x+2 | | 4+3r=5 | | y=y-b*x | | -19-21= | | Q^3-216Q=0 | | 9-(-23)= | | 3(x+1)/6=2x-1 | | x=8+2y | | -12x+2(x-5)+9=3x-10 | | 25/8+35/6 | | 1/8+y=4 | | u^2-12u+36=0 | | 220=-6x^2-37x+65 | | 5x-(2x-5)=20 | | 62=-42 | | 18v^2-33vb+14b^2=0 | | 160-2x=34+24x | | 17(6c-1)-4=100c+17 | | 3x+22=2x-15 | | [x+4]=3x-5 | | 15x^2+29xy-14y^2=0 | | 45(6+7x)= | | 45(6+7x)=9 |

Equations solver categories